Analisis peran Guru PPKn dalam menanamkan sikap Bela Negara pada Siswa Kelas X (Fase E) di SMA Negeri 4 Kota Jambi - Sianturi, Candro Genaro; Maulia, Siti Tiara; Salam, M.; Sariani, Dona (Academy of Education Journal, 2024)
This research departs from initial observations made by researchers at SMA Negeri 4 Jambi City, that class X (Phase E) students did not show an attitude of defending the country. This research aims to describe the role of PPKn teachers in instilling an attitude of defending the country in class . The approach to this research uses a qualitative approach and uses a qualitative descriptive research type. The data collection techniques used in this research are observation, interviews and documentation techniques.The results of this research show that PPKn teachers have carried out their role in instilling an attitude of defending the country, but there are several roles of PPKn teachers that have not been implemented by PPKn teachers, so the researcher concludes that PPKn teachers have not fully carried out their role well in accordance with the theory of the role of PPKn teachers put forward by Marzuki and Feriandi (2016:195), namely 1) Motivating Students, 2) Directing Students, 3) Initiator, 4) Informator, 5) Evaluator, 6) Facilitator. Then, the obstacles for PPKn teachers in instilling an attitude of defending the country in class X (Phase E) students at SMA Negeri 4 Jambi City are divided into 2 factors, namely internal and external factors. Internal factors are factors that come from within the student, such as a lack of student awareness. Then external factors are factors that are caused from outside the student, such as the student's background, the influence of social media and the student's environment.